Last best hope : America in crisis and renewal - Packer, George, 1960- (Farrar Straus & Giroux, 2021)
A National Book Award-winning author examines America's current descent into a failed state and discusses the ways we can leverage this moment to forge a new path forward that overcomes injustice, legislative paralysis, and political divides.